Pengelompokan Penanganan Resiko Pada Kegiatan Panen Berdasarkan Alat Pelindung Diri Yang digunakan : (Studi Kasus: PT. Langkat Nusantara Kepong Kebun Padang Brahrang) - Nur Fariza Khairani; Relita Buaton; Melda Pita Uli Sitompul (Modem : Jurnal Informatika dan Sains Teknologi., 2024)
Personal Protective Equipment (PPE) is essential for worker safety, especially in oil palm harvesting activities. PT Langkat Nusantara Kepong faces major challenges related to work safety, with analysis showing that work accidents still occur frequently in the Padang Brahrang Plantation. This indicates the need for an in-depth evaluation of the use of Personal Protective Equipment (PPE) to reduce the risk of work accidents. By using the clustering method to group data based on the type of Personal Protective Equipment (PPE) used and aims to provide recommendations for optimizing the use of personal protective equipment based on risk management and reducing the incidence of work accidents. From testing the results of cluster 3, cluster 4 and cluster 5 it can be concluded that clustering with 5 clusters provides the most efficient and precise results, followed by 4 clusters, while 3 clusters provide greater variation within clusters, indicating that clustering with fewer clusters is less able to capture subtle differences in the data.